Implementation Of Face Recognition In Employee Attendance System Case Study In Bandung Computer Education - Nita Aprianti; RR.Isni Puspowati; Asep Suherman; Resti Aulia Damayanti (LPPM STMIK Mardira Indonesia, 2025)
As technology advances, administrative activities, such as attendance management, have transitioned from manual techniques to digital platforms, facilitating more efficient access. At Bandung Computer Education, the employee attendance system remains manual, with attendance documented in Excel and evidence of attendance transmitted via WhatsApp. This procedure requires time for validation and does not ensure data security. The utilization of facial recognition technology serves as an efficient solution, facilitating automatic attendance tracking, minimizing the risk of mistakes, and managing data without manual entry in Excel or through photo verification using WhatsApp. This research seeks to create a face recognition-based attendance system that enhances accessibility for employees. This research encompasses the phases of system design and development, commencing with needs analysis and culminating in implementation. A needs analysis is conducted through surveys and interviews. The employed system development methodology is the prototype technique. The study's results indicate that the built facial recognition system has enhanced the accuracy of attendance recording and bolstered data security. This system is regarded as more accessible to employees.